Biocontrol potential of neem leaf-based vermicompost as indicated by chitinase, protease and β-1,3-glucanase activity - Loh, Khye Er; Nor Azwady Abdul Aziz; Muskhazli Mustafa; Intan Safinar Ismail (Penerbit Universiti Kebangsaan Malaysia, 2021)
The rising concern regarding the negative impact of synthetic pesticides has led to the search for alternative means of pest control. Vermicomposting the mixture of oil palm empty fruit bunch and neem (Azadirachta indica) leaves, with the latter known to have pesticidal value, is therefore of great interest and significance to be studied. The present study was conducted to evaluate the chitinase, protease and β-1,3-glucanase activity of neem leaf-based vermicompost as an indication of its biocontrol properties. The total microbial population of different composition of the vermicompost was also investigated. The results showed that at 10% neem composition, an increment in microbial population, chitinase and protease activities was observed in the end product. A higher concentration of neem exerted a suppressive effect on the microbial population as well as enzymatic activity. This study suggested that the addition of an appropriate composition of neem leaves as one of the raw materials for vermicomposting would potentially enhance the performance of vermicompost as biofertilizer as well as biopesticide.